2021
DOI: 10.31234/osf.io/e5mh9
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of different components of yoga: A review of comparative studies and meta-analyses

Abstract: Traditional yoga encompasses a variety of practices, such as physical postures, breathing techniques, meditation practices, and ethical teachings. Numerous studies and meta-analyses have demonstrated yoga’s efficacy in promoting mental and physical health. Conversely, little is known about how the diverse components of yoga contribute to its overall effect. In this review, we summarize the current evidence on the differential and incremental effects of yoga components. We evaluated 18 comparative studies and 1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…It is not easy to compare our findings to results of earlier studies. Although there have been some comparative or dismantling studies (Matko et al, 2021a), no study employed an additive design comparable to ours. Most studies compared rather complex interventions with each other, and only a few actually dismantled or added program components (e.g., Smith et al, 2011;Hunt et al, 2018).…”
Section: Framing Mantra Meditation Enhances Its Effectsmentioning
confidence: 80%
See 2 more Smart Citations
“…It is not easy to compare our findings to results of earlier studies. Although there have been some comparative or dismantling studies (Matko et al, 2021a), no study employed an additive design comparable to ours. Most studies compared rather complex interventions with each other, and only a few actually dismantled or added program components (e.g., Smith et al, 2011;Hunt et al, 2018).…”
Section: Framing Mantra Meditation Enhances Its Effectsmentioning
confidence: 80%
“…A recent review summarized comparative studies and meta-analyses of the effects of yoga components (Matko et al, 2021a ). The authors concluded that although most of the treatments compared were equal in length, outcomes were better for those that combined several elements of yoga practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoga, a mind-body exercise involving stretching, focus, and controlled breathing, has demonstrated bene ts for physical and mental health, including in healthy individuals [22,23]. Research indicates positive effects of yoga interventions on factors like cardiorespiratory endurance, exibility, muscular endurance, and balance in children [24].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars often discuss that yoga treats mind, body, and spirit as an integrated unit Tyberg (1940). The four main components of yoga in schools are voluntary breathing, purposeful movement, mindful meditation and relaxation (Butzer et al, 2015;Matko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%